Evaluation of foramen magnum in gender determination using helical CT scanning in Gwalior population - juglan, sarthak; Batham, I.K (International Journal of Medical Research and Review, 2016)
Background: Foramen magnum is the largest foramen in posterior cranial fossa. The present study was evaluated foramen magnum in gender determination using helical CT scanning in Gwalior population. Methods: 93 consensual patients (52 males and41females)from the department of radiology Gajra Raja Medical college, Gwalior, Madhya Pradesh were included in the study. Sagittal diameter, Transverse diameter of the Foramen magnum were measured. Results: The mean sagittal diameter of the foramen magnum was 36.7mm in males, 31.8mm in females and the transverse diameter was 33.8mm in males, 27.7 mm in females. Common shape of foramen magnum is rounded 33 (35.4%). Conclusion: It can be concluded from the result that the measurement of foramen magnum is suitable for sex determination.